Results of Anthropological Examination of the Material from the Cemetery in Ostow Lednicki - Kaźmierowska, Beata (Anthropological Review, 1988)
The work refers to the research carried out in 1978 and 1983-1985 on a series of 78 skeletons dating back to the 12th-13th centuries. The similarity between the series and the material excavacated in 1932-1935 was examined.